Geographic Concentration and Establishment Scale - Holmes, Thomas J.; Stevens, John J. (The Review of Economics and Statistics, 2002)
This paper shows that plants located in areas where an industry concentrates are larger, on average, than plants in the same industry outside such areas. In some sectors, such as manufacturing, the differences are substantial. The connection between size and concentration is stronger than what we would expect to find if plants were randomly distributed like darts on a dartboard.